2016
DOI: 10.1177/0300985816653792
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Unique Amyloid Sequence in AA Amyloidosis of a Pig Associated With Streptococcus Suis Infection

Abstract: Here we report a pig with amyloid A (AA) amyloidosis associated with Streptococcus suis infection and identification of a unique amyloid sequence in the amyloid deposits in the tissue. Tissues from the 180-day-old underdeveloped pig contained foci of necrosis and suppurative inflammation associated with S. suis infection. Congo red stain, immunohistochemistry, and electron microscopy revealed intense AA deposition in the spleen and renal glomeruli. Mass spectrometric analysis of amyloid material extracted from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Amyloid fibrils were extracted from formalin-fixed, paraffin-embedded duodenum with severe amyloid deposition (group A, quail No. 1) and digested with trypsin according to the method of Kamiie et al 9 The tryptic digests were subjected to nanoflow LCÀmass spectrometry (MS)/MS system equipped with an Orbi-Trap mass spectrometer (Orbi-Trap XL, Thermo Scientific, Boston, MA, USA) and queried according to the method of Taoka et al 33 The MS/MS data were converted to a Mascot generic format with the Proteome Discoverer software (Thermo Scientific, ver 1.1). The files were processed with the MASCOT algorithm (version 2.2.1, Matrix Science, London, UK) to assign peptides using the Swiss-Prot sequence database.…”
Section: Pathology Of Spontaneous Quail Aa Amyloidosismentioning
confidence: 99%
“…Amyloid fibrils were extracted from formalin-fixed, paraffin-embedded duodenum with severe amyloid deposition (group A, quail No. 1) and digested with trypsin according to the method of Kamiie et al 9 The tryptic digests were subjected to nanoflow LCÀmass spectrometry (MS)/MS system equipped with an Orbi-Trap mass spectrometer (Orbi-Trap XL, Thermo Scientific, Boston, MA, USA) and queried according to the method of Taoka et al 33 The MS/MS data were converted to a Mascot generic format with the Proteome Discoverer software (Thermo Scientific, ver 1.1). The files were processed with the MASCOT algorithm (version 2.2.1, Matrix Science, London, UK) to assign peptides using the Swiss-Prot sequence database.…”
Section: Pathology Of Spontaneous Quail Aa Amyloidosismentioning
confidence: 99%
“…In a porcine case report, splenic and renal AA amyloidosis were found in a pig that expressed an SAA2 sequence with 2 amino acid deletions (W2 and L3) and an L6V polymorphism. 16 In the cited case, fibrillization studies revealed that amyloid fibrils from the variant porcine SAA2 converted the wild-type SAA2 protein into amyloid fibrils. 16 In addition, the PROVEAN predictor rated the 2 deletions as "deleterious" and the L6V substitution as "neutral."…”
Section: Resultsmentioning
confidence: 97%
“…16 In the cited case, fibrillization studies revealed that amyloid fibrils from the variant porcine SAA2 converted the wild-type SAA2 protein into amyloid fibrils. 16 In addition, the PROVEAN predictor rated the 2 deletions as "deleterious" and the L6V substitution as "neutral." The G95 codon that is deleted in zebra finch A3 is not highly conserved in vertebrates (Figure 4), suggesting that this codon probably is not critical and was predicted by PROVEAN to be benign ( Table 2).…”
Section: Resultsmentioning
confidence: 97%
“…However, such antibodies do not exist for all animal species, and cross-reactivity with human and mouse antibodies is not universal. Mass spectrometry offers the ability to not only identify the type of amyloid in tissue but also sequence the protein and identify the potential variants or isoforms, as done by Kamiie et al 28 A reference proteome is needed, which are increasingly available across species through public databases (http://www.uniprot.org). 1 Beyond the use of mass spectrometry as a diagnostic tool, the research applications are vast, including protein profiling of amyloids and their associated proteins and identifying novel mutations not present in databases with the use of algorithms.…”
Section: Protein Sequencing By Mass Spectrometrymentioning
confidence: 99%
“…In people with rheumatoid arthritis, variants SAA1.1 (Caucasian) and SAA1.3 (Japanese) and a single nucleotide polymorphism (SNP) at -13(C/T) in the 5 0 UTR of SAA1 are associated with a greater likelihood of developing AA amyloidosis. 6,35,36,58 In this issue of Veterinary Pathology, Kamiie et al 28 present findings that implicate a variant SAA2 gene sequence in AA amyloid disease susceptibility in pigs. The variant was identified using protein sequencing by mass spectrometry of formalin-fixed paraffin-embedded (FFPE), amyloid-laden tissue from a pig with AA amyloidosis and confirmed as a variant of SAA2 by gene sequencing.…”
mentioning
confidence: 98%